2019
DOI: 10.1002/jcb.28458
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of semen quality and sperm‐DNA integrity as influenced by cigarette smoking in fertile and infertile human male smokers—A prospective study

Abstract: In modernized lifestyle smoking is one of the trendy, psychological, and socioeconomic scenarios of young adolescents mainly in the age of the reproductive stage. Based on a number of cigarettes smoked, age, and duration of the smoke, the study aims to search for the profound effects of smoking and its impact on semen parameters, sperm-DNA integrity, and fragmentation of sperm DNA with cotinine and apoptotic caspase-3 marker in the seminal plasma of fertile and infertile smokers. To determine oxidative damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 59 publications
2
16
2
1
Order By: Relevance
“…Among lifestyle factors, tobacco smoking has an adverse influence on sperm chromatin integrity (Aboulmaouahib et al, 2018;Boeri et al, 2019;Cui et al, 2016;Fraga et al, 1996;Gunes et al, 2018;Kumar et al, 2015;Mostafa et al, 2018;Ranganathan et al, 2019;Sharma, Harlev, et al, 2016). Cannabis consumption can also impair sperm DNA quality (Verhaeghe et al, 2020).…”
Section: Infertility Risk Factorsmentioning
confidence: 99%
“…Among lifestyle factors, tobacco smoking has an adverse influence on sperm chromatin integrity (Aboulmaouahib et al, 2018;Boeri et al, 2019;Cui et al, 2016;Fraga et al, 1996;Gunes et al, 2018;Kumar et al, 2015;Mostafa et al, 2018;Ranganathan et al, 2019;Sharma, Harlev, et al, 2016). Cannabis consumption can also impair sperm DNA quality (Verhaeghe et al, 2020).…”
Section: Infertility Risk Factorsmentioning
confidence: 99%
“…Various studies have been conducted linking several lifestyle factors/environmental exposures to elevated levels of SDF [78,94,[189][190][191][192][193][194][195][196][197][198]. These factors include (i) Physical agents such as radiation and heat; (ii) Chemical agents such as cigarette smoke, airborne pollutants, and chemotherapeutic drugs; and (iii) Biological factors including sexually transmitted infections, increasing male age, elevated body mass index (BMI) and medical conditions such as insulin dependent diabetes [78,94,[189][190][191][192][193][194][195][196][197][199][200][201]. Elevated OS levels is believed to be the main mechanism resulting in SDF with these exposures.…”
Section: High Risk Patientsmentioning
confidence: 99%
“…Exposure to environmental and lifestyle factors have far-reaching implications on male fertility. Current data has consistently associated smoking with higher SDF values when compared to non-smokers [91,99,191,215], however no study has yet evaluated the impact of smoking cessation on SDF. There have also been numerous environmental factors such as airborne pollutants, ionizing radiation, and pesticides linked with increased SDF values [74,82,193,216,217].…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…In the study of Najafipour and colleagues it was suggested that smoking can increase the methylation status of the miR-449 cluster's promoter (84). Other researchers have similarly associated smoking with aberrant methylation patterns in several genes as well as with abnormal semen parameters, indicating the detrimental epigenetic effect of smoking on male fertility (89)(90)(91). Evidence suggests that several other lifestyle parameters, physical activity levels, stress as well as aging are described as factors that could affect DNA methylome in spermatozoa, leading to abnormal methylation patterns in specific genome loci, including the miR-34/449 loci, eventually leading to structural and functional abnormalities of spermatozoa (86).…”
Section: Male Infertility In Humans and Mir-34/449 Associationsmentioning
confidence: 99%